If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3n + 1 = 3n + -2 Reorder the terms: 1 + -3n = 3n + -2 Reorder the terms: 1 + -3n = -2 + 3n Solving 1 + -3n = -2 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 1 + -3n + -3n = -2 + 3n + -3n Combine like terms: -3n + -3n = -6n 1 + -6n = -2 + 3n + -3n Combine like terms: 3n + -3n = 0 1 + -6n = -2 + 0 1 + -6n = -2 Add '-1' to each side of the equation. 1 + -1 + -6n = -2 + -1 Combine like terms: 1 + -1 = 0 0 + -6n = -2 + -1 -6n = -2 + -1 Combine like terms: -2 + -1 = -3 -6n = -3 Divide each side by '-6'. n = 0.5 Simplifying n = 0.5
| 6(n-2)-3(4-2n)=2n+16 | | M-1/8=4 | | 40y^-.6*x^.6-40((6y^.4)/5x^-.4) | | 1/2*1/2*2*2*2*2*2= | | 6=k/26 | | 7n/3=21 | | 3g+-2(g+4)=8(g+-1) | | 4+-(t+-24)+38t-38=0 | | 28+-6+x=40 | | 2/5=3/y-3 | | 18+-13+n=9 | | 8=1/2(3x-8) | | 3(4z-8)=6z-8 | | 25x-12=33 | | x/5-5=x/7- | | 45+36u=97+23u | | 12÷3/8= | | 8x+4(7-2x)= | | x-7=18+x | | x+1.3=0.6x | | -4(v-2)=-4(v-8)-v | | x+1.3=0.6 | | 12/30-2/5 | | -3(5x-3)=-6 | | 2x-6-(5x+1)=4-2x-(3x-1) | | x^2=14x+13 | | 8050=0.115x | | 5x-y=34 | | 4(3x-8)-10x-8=10 | | 167-8*4-23= | | 18x^4+69x^3-105x^2=0 | | 9-2a=53 |